Brain-derived neurotrophic factor and schizophrenia - Gören, Jessica L. (Ment Health Clin, 2016)
Schizophrenia is a severe disorder affecting approximately 1% of the population. Historically, alterations of dopaminergic function were considered the primary cause of schizophrenia. However, for many patients, drugs that alter dopaminergic function do not consistently lead to resolution of the symptoms of schizophrenia. Thus, there is an increased interest in pathophysiologic processes that result in altered neurodevelopment and plasticity associated with schizophrenia. Brain-derived neurotrophic factor (BDNF) is a neurotrophin involved in neurogenesis, synaptic plasticity, cognition, and neurotransmission. Genetic polymorphism, expression, and function of BDNF have been implicated in psychiatric diseases, including schizophrenia. This review discusses BDNF, its role in neurologic processes, and the evidence implicating BDNF in schizophrenia.